PRODUCTION OF STEVIOSIDE FROM CALLUS AND CELL SUSPENSION CULTURES OF STEVIA REBAUDIANA (BERT.) - S. Javad; S. Naz; S. Ilyas; A. Aftab (Journal of Animal and Plant Sciences, 2016)
Stevioside (a non-caloric natural sweetener) is extracted from Stevia rebaudiana, which isnative plant of South America. In present study, callus cultures of Stevia rebaudiana were established on MS medium fortified with different concentrations of BAP, 2,4-D and NAA and their combinations. Stevioside was then extracted from callus cultures by using microwave assisted extraction. Extracts were analyzed for presence of stevioside by using HPLC [C-18 column, flow rate 1ml/min, mobile phase methanol and water (80:20) and detection at spectrophotometer on 201nm]. Callus cultures produced on BAP or NAA supplemented media did not proliferate on subculturing while callus cultures established on media supplemented with 2,4-D produced very hard and brown cultures which were not suitable for cell suspension cultures. Friable green calli were produced on MS medium supplemented with BAP 1 mg/L, NAA 1 mg/L and 2,4-D 2.5 mg/L with maximum quantity of stevioside (33.87 mg per gram of plant material). Cell suspension cultures of S. rebaudiana were also established on same media with optimum conditions of pH 5.5, shaking speed of 80 rpm and subculturing interval of 30 days. It was concluded from present study that MS medium fortified with combination of BAP, NAA AND 2,4-D produced green calli of S. rebaudiana which can produce stevioside. These green callus cultures can also grow into cell suspension cultures and may be exploited for commercial scale production of stevioside.
Keywords: Stevioside; S. rebaudiana; Callus; Cell suspension cultures; BAP; NAA; 2; 4-D